UNESCO : current issues and challenges - Ali, Miyako (Government procedures and operations., 2018)
UNESCO: Current Issues and Challenges opens by examining the Convention on the Diversity of Cultural Expressions approved by UNESCO in 2005, which was intended to be the reference document for cultural diversity, but did not contemplate biological diversity. The concept of biological diversity is solidly formed while the concept of cultural diversity is barely systematized. Since its foundation in 1945, UNESCO has always advocated that education, science and culture are the paths for peace, which must be built upon respect for human rights. Therefore, the following chapter examines the UNESCO educational vision following the life cycle of a policy discussed in Jallade, Radi & Cuenin (2001), together with its mission of intellectual leadership, specialised knowledge, alliances, fair mediation and advanced monitoring. The policies necessary to make the aforementioned possible are also discussed. Following this, a digital project to improve the access to the UNESCO World Heritage Site of Mount Etna is presented. It proposes an interactive and multimedia catalog made with Google Street View technologies. The catalog can be browsable on a 360° virtual tour, "augmented" by specific aerial tours, captions with descriptive sheets and videos and enjoyable also in AR mode. The research presented in the final chapter estimates the net present value of a UNESCO World Heritage designation for three WH sites in Nova Scotia(NS), Canada. The research employs a cost-benefit analysis where economic benefits are defined as tourism related spending associated with the designation, and the costs include the application and ongoing expenses of the designation. It is concluded that the net present value of designation exhibits a high degree of heterogeneity among the sites considered.